Comparative study of ergonomic and technological criteria for universal accessibility at the Faculty of Architecture and Urbanism, Guayaquil, Ecuador - Seis, Luis; Pazmiño Franco, Carlos Cristobal; Guerrero Ferreccio, Carlos Augusto; Sagubay Bernal, Luis Antonio (Eximia, 2023)
Accessibility focused on people with reduced mobility has been a challenge for urban design in Latin America since these considerations are only met in 25% of public spaces in cities. Universal accessibility within the study centers is even more limited since the facilities do not have inclusive designs focused on people with reduced mobility. The University of Guayaquil was chosen as a case study, specifically the facilities of the Faculty of Architecture and Urbanism due to their spatial and architectural conditions. The objective of this study proposes the architectural redesign of public and buildable spaces with ergonomic and technological criteria that improve accessibility for people with disabilities. A qualitative and quantitative approach methodology is applied, evaluating the spatial and architectural conditions through weightings applied to ergonomic and technological criteria. As a result, it is obtained that the ergonomic criterion improves the conditions of users with physical disabilities by 60% according to adaptations of size and design and that the technological and communication information systems generate a better performance around disabilities. visual and auditory generating a 90% general improvement in users. As a future line of research, it is intended to extend these criteria to the rest of the faculties of the University of Guayaquil to obtain an inclusive model of higher education.